Internalization of magnetic iron oxide nanoparticles for stem cell functionalization - Gonçalves, A. I. (2014)
Cell monitoring and cell localization can be potentially achieved by the internalization of magnetic nanoparticles (MNPs) in the cells. This might allow for the investigation of migratory patterns through tracking studies, the targeting of particle-labelled cells to desired locations via the application of an external magnetic field and, finally, for activation stem cells to initiate desired cellular responses as inducing the differentiation process [1]. This study focus on determining the effect of magnetic stimulation in human adipose stem cells (hASCs) differentiation towards tendon cells. Firstly, the MNPs uptake by the cell and magnitude/frequency of the external magnetic field was verified. Afterwards, initial studies on understanding the endocytic mechanisms involved in the uptake of MNPs were performed. For this, cells were treated with pharmacological inhibitors before exposure to fluorescent labeled MNPs.